2009
DOI: 10.1126/science.1174811
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sulfur and Coking Tolerance of a Mixed Ion Conductor for SOFCs: BaZr 0.1 Ce 0.7 Y 0.2– x Yb x O 3–δ

Abstract: The anode materials that have been developed for solid oxide fuel cells (SOFCs) are vulnerable to deactivation by carbon buildup (coking) from hydrocarbon fuels or by sulfur contamination (poisoning). We report on a mixed ion conductor, BaZr(0.1)Ce(0.7)Y(0.2-)(x)Yb(x)O(3-delta), that allows rapid transport of both protons and oxide ion vacancies. It exhibits high ionic conductivity at relatively low temperatures (500 degrees to 700 degrees C). Its ability to resist deactivation by sulfur and coking appears lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
541
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,054 publications
(559 citation statements)
references
References 28 publications
12
541
4
2
Order By: Relevance
“…[7][8][9] In comparison, proton conducting oxides, many of which are perovskite-structured, offer higher ionic conductivity with low electronic transport number as well as lower activation energy at intermediate temperature. [10][11][12][13][14][15][16] As a result, they are regarded as the preferred electrolyte for IT-SOFC. 17 For IT-SOFC, the cathode process is generally regarded as the rate-limiting step due to its high activation energy compared to the electrolyte.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In comparison, proton conducting oxides, many of which are perovskite-structured, offer higher ionic conductivity with low electronic transport number as well as lower activation energy at intermediate temperature. [10][11][12][13][14][15][16] As a result, they are regarded as the preferred electrolyte for IT-SOFC. 17 For IT-SOFC, the cathode process is generally regarded as the rate-limiting step due to its high activation energy compared to the electrolyte.…”
Section: 2mentioning
confidence: 99%
“…7 In addition, how would the co-presence of H 2 O and CO 2 , which is a more realistic situation for practical SOFC operation, influence the electrochemical behavior for proton conducting SOFC with BSCF cathode has never been studied to the best of the authors' knowledge. 31,32 In this work, the chemical stability and compatibility of the BSCF cathode with one of the leading proton conducting electrolytes BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb) [10][11][12]14,15 under various conditions were studied. More importantly, BSCF/BZCYYb/BSCF cathode symmetrical cells were used to investigate the influence of water vapor and CO 2 on the electrochemical behaviors for the proton conducting IT-SOFC at various temperatures ranging from 650…”
Section: 2mentioning
confidence: 99%
“…To address this issue, two major approaches have been considered: using alternative anode materials with a high coking tolerance or co-feeding the fuel with a high concentration of oxidizing agents such as air, CO 2 , or water. [14][15][16][17][18][19] In our previous work we successfully produced a novel MoO 2 -based anode with an exceptionally high coking resistance for liquid hydrocarbons such as n-dodecane and biodiesel at an operating temperature of 850 8C. [20] The procedure developed in our group, which is based on the electrostatic spray deposition (ESD) method, has opened up the possibility of developing liquid hydrocarbon-fueled SOFCs.…”
mentioning
confidence: 99%
“…There was no evidence of carbonation when kept in flowing pure CO2 at 800 ºC for 24 hours and conductivity of 4 x 10 -3 S cm -1 at 600 ºC was measured, which is good enough for practical applications [31]. It showed a better densification as well and a relative density of ~ 95% after firing 1450 ºC, when processed via solid state reaction method; while for BZCY and BZCYYb, a sintering temperature 1550 ºC in required for getting a densification > 90% when processed by solid state reaction method [25,27].…”
Section: Introductionmentioning
confidence: 82%
“…However, later it has been reported that BZCY was unstable when it was kept in 3% (balanced with air) CO2 at 600 ºC for 24 hours and diffraction peaks corresponding to BaCO3 and CeO2 were observed in XRD [26]. Aliovalent Y + Yb co-doped BCZY showed better performance than BZCY and higher ionic conductivity of 14 x 10 -3 S cm -1 at 500 ºC [27,28]. However, though initially BaZr0.1Ce0.7Y0.2Yb0.1O3 -δ (BZCYYb) was reported to be stable in CO2 atmospheres, later it was found to be unstable when heated up to 800 ºC in CO2/N2 (1:2 ratio) atmosphere [29].…”
Section: Introductionmentioning
confidence: 99%